2017
DOI: 10.4314/gjedr.v16i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Headteachers’ managerial behaviour and teachers’ task performance in public primary schools in Calabar-South local government area, Cross river state, Nigeria

Abstract: This study aimed at Investigating Head teachers' Managerial Behaviour and Teachers' Task Performance in Public Primary Schools in Calabar-South L.G.A. of Cross River State. Three (3) hypotheses were formulated and tested in the study. The survey research design was adopted for the study. The study population comprised all the head teachers and deputy head teachers in the twenty one (21) public primary schools in Calabar-South L.G.A. The twenty one (21) head teachers and twenty one (21) deputy head teachers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
1
7
1
Order By: Relevance
“…This implies that the more democratic a school head is, the more teachers’ role performance also increases. However, this study finding is inconsistent with the findings of a study by Mbon (2017) that revealed that headteachers’ leadership style had no significant influence on teachers’ task performance. This means that in the context of Mbon’s study the use of people- or task-oriented management style by the headteacher had no effect on teachers’ task performance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This implies that the more democratic a school head is, the more teachers’ role performance also increases. However, this study finding is inconsistent with the findings of a study by Mbon (2017) that revealed that headteachers’ leadership style had no significant influence on teachers’ task performance. This means that in the context of Mbon’s study the use of people- or task-oriented management style by the headteacher had no effect on teachers’ task performance.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas the extent to which various management styles are employed by headteachers in some contexts is known, there is no such data on headteachers of secondary schools in Tororo District. Given that the performance of teachers, learners, and other stakeholders in any school is directly linked to the managerial behavior of the school head (Mbon, 2017), the authors purposed to garner data on management styles of the headteachers of the secondary schools in Tororo District so as to determine any possible linkages. The objectives of the study included the following:…”
Section: Introductionmentioning
confidence: 99%
“…Also, head teachers' communication skills significantly relate to teachers' task performance in the area. Proper managerial behavior to boost teachers' morale towards high task performance has to be adopted [25]. [26] found that differences and relationships exist between teachers and principals in terms of how much they believe specific leadership practices influence school performance.…”
Section: Introductionmentioning
confidence: 99%
“…During the staff meeting and to provide a forum for direct communication with both teaching and non-teaching staff, the school head must summon a regular meeting so that the teaching and learning goals could be achieved (Agih, 2015). Usen (2017) reiterated that school efficiency and effectiveness can only be enhanced if there is a collaboration between the principal and teaching staff as well as good use of administrative communication between educators and learners. A principal or headteacher is expected to be effective by encouraging teamwork, creating constructive knowledge and a learning community in which each member develops.…”
Section: Introductionmentioning
confidence: 99%